Edge Degree Weight of Sequential Join of Graphs - Sharaf, Khidir R.; Ali, Didar A. (Science Journal of University of Zakho, 2013)
Let the weight w of an edge e= uv=u,v of a graph G be defined by w(e)=deg(u)+deg(v)-2 and the weight of G be defined by w(G)= ∑ e ∈ E(G)w(e), where E(G) is the edge set of G. In this paper the weights of joins, sequential joins, unions, intersections, and products (Cartesian and Tensor) of sets of graphs are obtained. This leads to a variety of open questions and new studies.